Perbandingan Hukum Ketenagakerjaan Indonesia dan Malaysia - Vedita Akbar; Handar Subhandi Bakhtiar (STIKes Ibnu Sina Ajibarang, 2025)
This study discusses the comparison of labor law between Indonesia and Malaysia, focusing on the regulation of employment relations, worker protection, wage systems, and outsourcing practices. Indonesia, through Law Number 6 of 2023, strengthens labor regulations by emphasizing worker protection, whereas Malaysia, through the Employment Act 1955, emphasizes flexibility in employment relationships with minimum protection. This research uses normative legal research methods and a comparative law approach. The results show that Indonesia prioritizes structural and formal worker protection, while Malaysia emphasizes administrative efficiency. This study recommends strengthening worker protection in both countries and the need for harmonization of labor standards within the ASEAN region.